Silicon-carbon composite material as well as preparation method and application thereof
By forming silicon-containing particles on the porous carbon matrix by vapor deposition and covering aluminum silicate and carbon layer, the performance degradation of silicon-based anode material in lithium-ion batteries due to volume changes and SEI film instability is solved, and a higher battery efficiency and capacity retention rate is achieved.
Patent Information
- Application Number
- CN202411616845.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-25
AI Technical Summary
The silicon-based negative electrode material in lithium-ion batteries causes the electrode material to powder and collapse in structure due to volume changes, and an unstable SEI film is formed when in contact with the electrolyte, resulting in irreversible capacity loss and degradation of battery performance.
Porous carbon is used as the matrix, silicon-containing particles are formed on its surface and pores by vapor deposition, and aluminum silicate layer is coated on the surface of the silicon-containing particles, and finally a carbon layer is coated on the surface of the porous carbon to form a silicon-carbon composite material.
The first Coulomb efficiency and capacity retention rate of lithium-ion batteries are improved, and the pole expansion rate is reduced, improving the mechanical stability and electronic conductivity of the battery.
Smart Images

Figure BDA0005132454740000071 
Figure BDA0005132454740000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials, and in particular to a silicon-carbon composite material and a preparation method and application thereof. Background Art
[0002] At present, the gram capacity of commercial graphite anode materials has reached 360-365mAh / g, which is close to its theoretical gram capacity of 372mAh / g. Therefore, it has become an urgent need to replace traditional graphite anodes with high specific capacity anode materials to achieve higher energy density lithium-ion batteries. Although silicon-based anode materials have a theoretical capacity of up to 3580mAh / g, they undergo significant volume changes during the insertion and extraction of lithium ions, resulting in pulverization of electrode materials and structural collapse. In addition, when silicon-based anodes come into contact with electrolytes, they form unstable SEI films, which are easily broken and rebuilt during the cycle, consuming lithium sources and electrolytes, resulting in irreversible capacity loss. At the same time, the reaction of silicon-based anode materials with electrolytes will produce by-products, increase the impedance of the electrodes, and further reduce battery performance. These factors together limit the promotion of silicon-based anode materials in commercial applications.
[0003] At present, the performance of silicon-carbon composite particles is often improved by coating them with a layer of carbon; however, the carbon layer is prone to rupture during long-term cycles, resulting in the exposure of silicon and failing to effectively prevent the occurrence of interface side reactions. In addition, during the carbon coating process, since silicon is in an amorphous state, it is easy to react with the carbon source to form byproducts such as SiC, which not only reduces the initial efficiency of the material, but also increases polarization.
[0004] Although the silane deposition method has been used to solve the related problems, the cycle retention rate of the obtained silicon-carbon negative electrode material is still insufficient. In other words, although the silane deposition method has been used to improve the performance of silicon-carbon negative electrode materials, the retention rate of these materials during the cycle use process is still low. Summary of the invention
[0005] Based on the technical problems existing in the background technology, the present invention proposes a silicon-carbon composite material and a preparation method and application thereof. When the silicon-carbon composite material of the present invention is used in a lithium-ion battery, the initial coulombic efficiency and capacity retention rate of the lithium-ion battery can be improved, and the pole piece expansion rate can be reduced.
[0006] The present invention provides a silicon-carbon composite material, comprising: porous carbon, silicon-containing particles distributed on the surface and inside the pores of the porous carbon, an aluminum silicate layer coated on the surface of the silicon-containing particles, and a carbon layer coated on the surface of the porous carbon.
[0007] Preferably, the porous carbon is porous hard carbon.
[0008] The above-mentioned porous hard carbon includes but is not limited to phenolic resin carbide, fruit shell biochar, etc.
[0009] Preferably, the particle size of the porous carbon is 5-60 μm.
[0010] Preferably, the pore volume of the porous carbon is 0.5-1.0 m 3 / g.
[0011] Preferably, the specific surface area of the porous carbon is 1000-2500m 2 / g.
[0012] Preferably, the silicon content in the silicon-carbon negative electrode composite material is 25-75wt%.
[0013] Preferably, the oxygen content in the silicon-carbon negative electrode composite material is 0.1-5 wt %.
[0014] Preferably, the aluminum content in the silicon-carbon negative electrode composite material is 0.1-5wt%.
[0015] Preferably, the silicon-containing particles include: nano-silicon and nano-silicon oxide.
[0016] Preferably, the weight ratio of the silicon-containing particles distributed in the pores of the porous carbon to the silicon-containing particles distributed on the surface of the porous carbon is 8.5-9.5:0.5-1.5.
[0017] The present invention also proposes a method for preparing the silicon-carbon composite material, comprising the following steps: sequentially performing vapor deposition on porous carbon using silane, aluminum vapor, and vapor-phase carbon to obtain the silicon-carbon composite material.
[0018] Preferably, the vapor deposition is performed in a vapor deposition apparatus.
[0019] The above-mentioned vapor deposition equipment can be a rotary furnace, a fluidized bed, etc.
[0020] Preferably, the carrier gas during vapor deposition is nitrogen or argon.
[0021] Preferably, the silane is at least one of monosilane and disilane.
[0022] Preferably, when vapor deposition is performed using silane, the rotation speed of the vapor deposition equipment is 0.5-1.5 rpm.
[0023] Preferably, when silane is used for vapor deposition, the deposition temperature is 450-500° C. and the deposition time is 5-7 hours.
[0024] Preferably, when silane is used for vapor deposition, the flow rate ratio of silane to carrier gas is 2-3:0.8.
[0025] Preferably, when silane is used for vapor deposition, the flow rate of silane is 2-3 L / min.
[0026] Preferably, when vapor deposition is performed using silane, the ratio of the porous carbon weight to the silane flow rate is 2-2.5 kg: 2-3 L / min.
[0027] Preferably, after the silane vapor deposition, a passivation treatment is performed.
[0028] Preferably, the passivation treatment step includes: cooling to 350-400° C., introducing carrier gas and oxygen, and heat preservation and passivation for 1-2 hours.
[0029] Preferably, the flow rate ratio of carrier gas to oxygen is 2-3:0.5.
[0030] Preferably, the flow rate of the carrier gas is 2-3 L / min.
[0031] Preferably, the ratio of the porous carbon weight to the carrier gas flow rate is 2-2.5 kg: 2-3 L / min.
[0032] Preferably, when aluminum vapor is used for vapor deposition, the deposition temperature is 600-900° C. and the time is 1-2 hours.
[0033] Preferably, when the aluminum vapor is used for vapor deposition, the aluminum vapor is transported by a carrier gas for vapor deposition.
[0034] Preferably, when aluminum vapor is used for vapor deposition, the carrier gas flow rate is 0.4-0.6 L / min.
[0035] Preferably, aluminum powder is vaporized into aluminum vapor, and the weight ratio of aluminum powder to porous carbon is 0.005-0.015:1.
[0036] Preferably, the gas phase carbon is acetylene.
[0037] Preferably, when vapor phase carbon is used for vapor phase deposition, the deposition temperature is 600-800° C. and the deposition time is 1.5-2.5.
[0038] Preferably, when vapor phase carbon is used for vapor deposition, the flow rate ratio of vapor phase carbon to carrier gas is 0.8-1.2:0.5.
[0039] Preferably, when vapor phase carbon is used for vapor deposition, the flow rate of the vapor phase carbon is 0.8-1.2 L / min;
[0040] Preferably, when vapor deposition is performed using vapor phase carbon, the ratio of the porous carbon weight to the vapor phase carbon flow rate is 2-2.5 kg: 0.8-1.2 L / min.
[0041] The present invention also proposes the application of the silicon-carbon composite material in negative electrode materials.
[0042] The present invention uses silane to perform vapor deposition on porous carbon, thereby forming silicon-containing particles on the surface and in the pores of the porous carbon. After passivation treatment, aluminum vapor is used for vapor deposition, so that the passivation layer on the surface of the silicon-containing particles reacts with the aluminum vapor to form an aluminum silicate phase with a higher elastic modulus, which can effectively fill the defect sites in the material, improve the mechanical stability and electronic conductivity of the silicon-carbon negative electrode composite material, and inhibit the polarization and volume expansion of the silicon-carbon negative electrode composite material during the charge and discharge process; and then the silicon-carbon composite material is coated with vapor phase carbon to further improve the electrical properties and improve the volume expansion.
[0043] In addition, the present invention can control the deposition position of silane in porous carbon by adjusting the parameters of silane vapor deposition, so that more silicon-containing particles are deposited inside the pores of the porous carbon rather than on the surface; the problem of excessive deposition of silicon-containing particles on the surface or uneven deposition during silane deposition can be effectively avoided. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is described in detail below through specific embodiments.
[0045] Example 1
[0046] A method for preparing a silicon-carbon composite material comprises the following steps:
[0047] Weigh 2 kg of porous coconut shell biochar (with a specific surface area of 1800 cm 2 / g, pore volume is 0.75m 3 / g, particle size 6-15μm), baked under vacuum at 100°C for 10h, and placed in a rotary kiln after drying;
[0048] The furnace tube speed was adjusted to 1.5 rpm, the temperature was raised to 475° C., a mixed gas of monosilane and nitrogen was introduced (wherein the flow rate of monosilane was 2.5 L / min, and the flow rate of nitrogen was 0.8 L / min), and vapor deposition was performed at a constant temperature for 6 h, and the introduction of the mixed gas of monosilane and nitrogen was stopped;
[0049] The temperature was lowered to 375°C, and a nitrogen and oxygen mixed gas was introduced (wherein the flow rate of nitrogen was 2.5 L / min and the flow rate of oxygen was 0.5 L / min), and the mixture was passivated at a constant temperature for 1 h, and the introduction of the nitrogen and oxygen mixed gas was stopped;
[0050] The temperature was raised to 700°C, and aluminum vapor was introduced into the rotary furnace (20 g aluminum powder was added into the vacuum furnace, and the temperature was raised to 600°C until the aluminum powder was completely vaporized to obtain aluminum vapor; 0.5 L / min nitrogen was introduced to carry the aluminum vapor into the rotary furnace, and the vapor deposition was carried out at a constant temperature for 1 hour, and the introduction of aluminum vapor was stopped;
[0051] A mixed gas of nitrogen and acetylene (the flow rate of nitrogen is 0.5 L / min, and the flow rate of acetylene is 1 L / min) is introduced into the rotary furnace, and vapor deposition is carried out at a constant temperature of 700°C for 2 hours. The introduction of acetylene is stopped and the temperature is cooled to room temperature to obtain a silicon-carbon composite material.
[0052] The silicon-carbon composite material obtained in Example 1 was tested, and it was found that: silicon-containing particles were distributed on the surface and inside the pores of the porous hard carbon (the silicon-containing particles included nano-silicon and nano-silicon oxide; the weight ratio of the silicon-containing particles inside the pores to the silicon-containing particles on the surface of the porous carbon was 9:1), the surface of the silicon-containing particles was coated with an aluminum silicate layer, and the surface of the porous carbon was coated with a carbon layer; the silicon content in the silicon-carbon negative electrode composite material was 50wt%, the oxygen content was 1wt%, and the aluminum content was 1wt%.
[0053] Example 2
[0054] A method for preparing a silicon-carbon composite material comprises the following steps:
[0055] Weigh 2 kg of porous coconut shell biochar (with a specific surface area of 1800 cm 2 / g, pore volume is 0.75m 3 / g, particle size 6-15μm), baked under vacuum at 100°C for 10h, and placed in a rotary kiln after drying;
[0056] The furnace tube speed was adjusted to 1.5 rpm, the temperature was raised to 500° C., a mixed gas of disilane and nitrogen was introduced (wherein the flow rate of disilane was 2 L / min, and the flow rate of nitrogen was 0.8 L / min), and vapor deposition was performed at a constant temperature for 5 h, and the introduction of the mixed gas of disilane and nitrogen was stopped;
[0057] The temperature was lowered to 400°C, and a mixture of nitrogen and oxygen was introduced (the flow rate of nitrogen was 2.5 L / min, and the flow rate of oxygen was 0.5 L / min), and the mixture was passivated at a constant temperature for 1 h, and the introduction of the mixture of nitrogen and oxygen was stopped;
[0058] The temperature was raised to 800°C, and aluminum vapor was introduced into the rotary furnace (30 g aluminum powder was added into the vacuum furnace, and the temperature was raised to 600°C until the aluminum powder was completely vaporized to obtain aluminum vapor; 0.5 L / min nitrogen was introduced to carry the aluminum vapor into the rotary furnace, and the vapor deposition was carried out at a constant temperature for 1 hour, and the introduction of aluminum vapor was stopped;
[0059] A mixed gas of nitrogen and acetylene (the flow rate of nitrogen is 0.5 L / min, and the flow rate of acetylene is 1 L / min) is introduced into the rotary furnace, and vapor deposition is carried out at a constant temperature of 800°C for 1.5 hours. The introduction of acetylene is stopped and the temperature is cooled to room temperature to obtain a silicon-carbon composite material.
[0060] Example 3
[0061] A method for preparing a silicon-carbon composite material comprises the following steps:
[0062] Weigh 2.5 kg of porous coconut shell biochar (with a specific surface area of 1800 cm 2 / g, pore volume is 0.75m 3 / g, particle size 6-15μm), baked under vacuum at 100°C for 10h, and placed in a rotary kiln after drying;
[0063] The furnace tube speed was adjusted to 1.5 rpm, the temperature was raised to 450° C., a mixed gas of monosilane and nitrogen was introduced (wherein the flow rate of monosilane was 3 L / min, and the flow rate of nitrogen was 0.8 L / min), and vapor deposition was performed at a constant temperature for 7 h, and the introduction of the mixed gas of monosilane and nitrogen was stopped;
[0064] The temperature was lowered to 350°C, and a nitrogen and oxygen mixed gas was introduced (where the flow rate of nitrogen was 2.5 L / min and the flow rate of oxygen was 0.5 L / min), and the mixture was passivated at a constant temperature for 2 h, and the introduction of the nitrogen and oxygen mixed gas was stopped;
[0065] The temperature was raised to 700°C, and aluminum vapor was introduced into the rotary furnace (20 g aluminum powder was added into the vacuum furnace, and the temperature was raised to 600°C until the aluminum powder was completely vaporized to obtain aluminum vapor; 0.5 L / min nitrogen was introduced to carry the aluminum vapor into the rotary furnace, and the vapor deposition was carried out at a constant temperature for 2 h, and the introduction of aluminum vapor was stopped;
[0066] A mixed gas of nitrogen and acetylene (the flow rate of nitrogen is 0.5 L / min, and the flow rate of acetylene is 1 L / min) is introduced into the rotary furnace, and vapor deposition is carried out at a constant temperature of 600°C for 2.5 hours. The introduction of acetylene is stopped and the temperature is cooled to room temperature to obtain a silicon-carbon composite material.
[0067] Comparative Example 1
[0068] Without passivation treatment, after silane vapor deposition, aluminum vapor and vapor carbon deposition are directly carried out in sequence, and the specific parameters are the same as those in Example 1.
[0069] Comparative Example 2
[0070] Without aluminum vapor deposition, vapor phase carbon deposition is directly performed after passivation, and the specific parameters are the same as those in Example 1.
[0071] Comparative Example 3
[0072] The temperature of silane vapor deposition is 525° C., and the rest is the same as in Example 1.
[0073] Comparative Example 4
[0074] During silane vapor deposition, the flow rate of silane was 5 L / min, and the other steps were the same as in Example 1.
[0075] The materials obtained in Examples 1-3 and Comparative Examples 1-4 were used as negative electrode materials, and the negative electrode materials, binders (CMC) and conductive agents (SuperP) were mixed in a weight ratio of 8:1:1 to prepare negative electrode slurry and coated on the surface of copper foil, vacuum dried at 100°C for 12 hours, and finally punched with a punching machine to obtain a button negative electrode sheet with a diameter of 12 mm; lithium metal was used as the positive electrode, Celgard2400 was used as the diaphragm, and 1 mol / L LiPF6 solution was used as the electrolyte (the solvent was EC:DMC=1:1v / v, and the electrolyte also contained 10wt% FEC as an additive), and 2032 button batteries were assembled in a glove box under a high-purity argon environment. The performance of each group of batteries was tested, and the results are shown in Table 1.
[0076] The first charge and discharge curves were tested at a voltage of 0.005-1.5V; the capacity retention rate at 0.02C was tested.
[0077] The first electrode expansion rate = the thickness of the active material layer after the first lithium removal / the thickness of the active material layer before lithium insertion.
[0078] Table 1 Test results
[0079]
[0080]
[0081] It can be seen from Example 1 and Comparative Examples 1-2 that without passivation treatment or aluminum vapor deposition, the initial coulombic efficiency and capacity retention rate of the battery are both low, and the initial pole piece expansion rate is high;
[0082] It can be seen from Example 1 and Comparative Example 3 that low-temperature deposition can effectively improve the initial efficiency and capacity retention rate of the battery; this is because a higher deposition temperature will accelerate the deposition rate of silane, thereby forming too much silane layer on the surface of the substrate and making the silicon particles in the substrate too large; this not only leads to a higher battery capacity and lower initial efficiency, but also increases the expansion of the battery during the cycle; in the repeated repair process of the SEI film, a large amount of Li + is consumed, thus significantly reducing the cycle life of the battery;
[0083] It can be seen from Example 1 and Comparative Example 4 that the size of the silane flow rate has a significant impact on the material properties. A lower flow rate will result in too little silicon deposition, while a higher flow rate will cause the silicon-containing particles to agglomerate, reduce the ability to deintercalate and deintercalate lithium, and reduce the first effect.
[0084] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A silicon-carbon composite material, characterized in that: include: Porous carbon, silicon-containing particles are distributed on the surface and inside the pores of the porous carbon, an aluminum silicate layer is coated on the surface of the silicon-containing particles, and a carbon layer is coated on the surface of the porous carbon.
2. The silicon-carbon composite material according to claim 1, characterized in that: The porous carbon is porous hard carbon; preferably, the particle size of the porous carbon is 5-60 μm; preferably, the pore volume of the porous carbon is 0.5-1.0 m 3 / g; preferably, the specific surface area of the porous carbon is 1000-2500m 2 / g.
3. The silicon-carbon composite material according to claim 1 or 2, characterized in that: The silicon content in the silicon-carbon negative electrode composite material is 25-75wt%; preferably, the oxygen content in the silicon-carbon negative electrode composite material is 0.1-5wt%; preferably, the aluminum content in the silicon-carbon negative electrode composite material is 0.1-5wt%.
4. The silicon-carbon composite material according to any one of claims 1 to 3, characterized in that: The silicon-containing particles include: nano-silicon and nano-silicon oxide; preferably, the weight ratio of the silicon-containing particles distributed inside the porous carbon pores to the silicon-containing particles distributed on the surface of the porous carbon is 8.5-9.5:0.5-1.
5.
5. A method for preparing the silicon-carbon composite material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: using silane, aluminum vapor and gas phase carbon to sequentially perform gas phase deposition on porous carbon to obtain a silicon-carbon composite material.
6. The method for preparing the silicon-carbon composite material according to claim 5, characterized in that: The vapor deposition is carried out in a vapor deposition device; preferably, the carrier gas during the vapor deposition is nitrogen or argon.
7. The method for preparing the silicon-carbon composite material according to claim 6, characterized in that: The silane is at least one of monosilane and disilane; preferably, when silane is used for vapor deposition, the rotation speed of the vapor deposition equipment is 0.5-1.5 rpm; preferably, when silane is used for vapor deposition, the deposition temperature is 450-500°C and the deposition time is 5-7h; preferably, when silane is used for vapor deposition, the flow rate ratio of silane to carrier gas is 2-3:0.8; preferably, when silane is used for vapor deposition, the flow rate of silane is 2-3 L / min; preferably, when silane is used for vapor deposition, The ratio of the porous carbon weight to the silane flow rate is 2-2.5kg:2-3L / min; preferably, after the silane vapor deposition, the passivation treatment is carried out; preferably, the passivation treatment steps include: cooling to 350-400°C, introducing carrier gas and oxygen, and keeping warm for passivation for 1-2h; preferably, the flow rate ratio of the carrier gas and oxygen is 2-3:0.5; preferably, the flow rate of the carrier gas is 2-3L / min; preferably, the ratio of the porous carbon weight to the carrier gas flow rate is 2-2.5kg:2-3L / min.
8. The method for preparing the silicon-carbon composite material according to claim 6 or 7, characterized in that: When aluminum vapor is used for vapor deposition, the deposition temperature is 600-900°C and the time is 1-2h; preferably, when aluminum vapor is used for vapor deposition, the aluminum vapor is transported by a carrier gas for vapor deposition; preferably, when aluminum vapor is used for vapor deposition, the carrier gas flow rate is 0.4-0.6L / min; preferably, aluminum powder is vaporized into aluminum vapor, and the weight ratio of aluminum powder to porous carbon is 0.005-0.015:
1.
9. The method for preparing the silicon-carbon composite material according to any one of claims 6 to 8, characterized in that: The gaseous carbon is acetylene; preferably, when gas phase carbon is used for vapor deposition, the deposition temperature is 600-800°C and the time is 1.5-2.5; preferably, when gas phase carbon is used for vapor deposition, the flow rate ratio of gas phase carbon and carrier gas is 0.8-1.2:0.5; preferably, when gas phase carbon is used for vapor deposition, the flow rate of gas phase carbon is 0.8-1.2L / min; preferably, when gas phase carbon is used for vapor deposition, the ratio of porous carbon weight to gas phase carbon flow rate is 2-2.5kg:0.8-1.2L / min.
10. Use of the silicon-carbon composite material according to any one of claims 1 to 4 in negative electrode materials.
Citation Information
Patent Citations
Preparation method and application of metal and carbon coaxial fiber and macroscopic body thereof
CN114775272A
Method for producing aluminum-silicon intermediate alloy through vapor deposition
CN116411198A
Silicon-carbon composite material and preparation method thereof, lithium ion battery and electronic equipment
CN116504986A
Silicon-carbon negative electrode material and preparation and application thereof
CN116995220A
Silicon-carbon negative electrode composite material, preparation method and application thereof, and battery
CN117790738A
Cited By
High-energy silicon-carbon composite negative electrode material for lithium ion battery and preparation process of high-energy silicon-carbon composite negative electrode material
CN120348941A
Silicon-carbon negative electrode material, preparation method thereof and secondary battery
CN120690848A
Biomass carbon for positive electrode of lithium-sulfur battery as well as preparation method and application of biomass carbon
CN121134735A
Biomass carbon for lithium-sulfur battery cathode and preparation method and application thereof
CN121134735B